Conflict Resolution and Peace Education in Africa - Uwazie, Ernest E., 1960- (Lanham, Md. : Lexington Books, 2003)
"Africa today suffers from too much political unrest and violent conflict. The contributors to this edited collection recognize a missing link in efforts to foster democracy, and with it political stability and peace, in Africa's developing countries. Democracy can be sustained only where effective means for resolving citizens' disputes exist both inside and outside the formal legal system. These scholars, practitioners, and peace advocates present their varied knowledge of conflict and war in Africa, as well as strategies for introducing and implementing mediation from Sierra Leone to South Africa. This volume is a model exchange of insights and ideas in the important field of conflict resolution as it applies to Africa."--BOOK JACKET.
Preface: Conflict Resolution and Peace Education in Africa: Lessons and Prospects / Ernest E. Uwazie -- Ch. 1. Conflict Resolution and Peace Education in Africa: An Introduction / Ernest E. Uwazie -- Ch. 2. Conflict Resolution and Peace Education in Africa: Lessons and Opportunities / Chris Bakwesegha -- Ch. 3. An Elusive Quest? Structural Analysis of Conflicts and Peace in Africa / Kelechi Kalu -- Ch. 4. The Economic Impact of Africa's Conflicts / George N. Ayittey -- Ch. 5. Educated in War: The Rehabilitation of Child Soldiers in Sierra Leone / Susan Shepler -- Ch. 6. Safe Schools: Violence and the Struggle for Peace and Democracy in South African Education / Clive Harber -- Ch. 7. Igbo Women and the Tradition of Peace: The Dynamics of Change and Continuity / Rose Acholonu -- Ch. 8. A Critical Perspective of U.S. Policy in the Central African Region: The Case for an Early Conflict Warning System / Peter Wanyama Madaka -- Ch. 9. Teaching and Learning about Human Rights in Postconflict Angola / Tracey Holland -- Ch. 10. Toward a Framework for a Model of Peace Education in Nigeria / Derry-Joe M. Yakubu -- Ch. 11. Peaceful Conflict Resolution: A Prerequisite for Social Reconstruction in Burundi, Africa / Elavie Ndura -- Ch. 12. Managing Political and Ethnic Diversity in Sub-Saharan Africa / Robert Dibie.
Includes bibliographical references and index.
Keywords: Conflict management -- Africa; Peace -- Study and teaching -- Africa; Education -- Social aspects -- Africa; Africa -- Politics and government -- 1960-